Conditions Required for Relief Formation of Iridescent Hologram - V. V. Zvereva (Наука и техника)
Purpose of the paper is to reveal optimization of parameters concerning arrangement of cameras relative to an object model in 3DStudioMAX for the subsequent formation of iridescent hologram. The paper gives the main regularities and principles of camera arrangement relative to a computer model with the purpose to obtain a qualitative 3D hologram image.